2010
DOI: 10.1100/tsw.2010.45
|View full text |Cite
|
Sign up to set email alerts
|

Empyema of the Ureteral Stump. An Unusual Complication Following Nephrectomy

Abstract: A ureteral stump, which is the segment of the ureter left in place after nephrectomy, may occasionally give rise to a pathologic process called ureteral stump syndrome, which is clinically interpreted as febrile urinary tract infections, lower quadrant pain, and hematuria. Empyema of the ureteral stump, which belongs to this syndrome, is an uncommon disease entity presenting with a reported incidence of 0.8–1%. We present a case of empyema of the ureteral stump in a female patient 5 years postnephrectomy for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…Ureteral stump empyema is an uncommon variant of ureteral stump syndrome [6, 7]. It evolves from retained pus in an obstructed stump [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ureteral stump empyema is an uncommon variant of ureteral stump syndrome [6, 7]. It evolves from retained pus in an obstructed stump [3].…”
Section: Discussionmentioning
confidence: 99%
“…When a constellation of symptoms including fever, lower abdominal pain, irritative lower urinary tract symptoms, and hematuria results from the ureteral stump, it is known as the “ureteral stump syndrome” [4]. Moreover, suppuration may develop forming a rare variant known as the “ureteral stump empyema” [5-7]. The question is whether preserving the potential site of kidney transplantation surgically fresh deserves leaving the ureteral stump for a later session.…”
Section: Introductionmentioning
confidence: 99%
“…Following nephrectomy, US with good drainage eventually undergo muscular atrophy. If the US continues to suffer repeated episodes of urinary reflux, it may lead to gross dilatation with urine not effectively drained [2,5,6]. However, Escolino et al [4] found that even a relatively short US (3 cm) could become symptomatic due to reflux.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of patients are asymptomatic but when reflux into the stump produces recurrent febrile urinary tract infections, bacteriuria or hematuria, empyema, stones or even malignancy, the condition is call ureteral stump syndrome [1,2]. It is a rare entity with an incidence of 1.1-10% usually occurring many years after surgery [3].…”
Section: Introductionmentioning
confidence: 99%
“…Nonrefluxing ureteral stumps are very unlikely to become dilated and cause symptoms [6]. Nevertheless, cases of empyema of the stump have also been described [7], and the 2 conditions can be confused at times [8][9][10].…”
Section: Discussionmentioning
confidence: 99%